(untitled) (Western Journal of Medical and Biomedical Sciences, 2023)
Breastfeeding practices, including initiation and duration, are influenced by interwoven factors which include health, psychosocial, cultural etc. As a result of rapid changes in the socio-cultural and economic situations worldwide, the need for income activity for women has increased. The study aimed to determine the practice and challenges of exclusive breastfeeding EBF among working-class mothers in Ogbomoso. The study was carried out among two hundred and twenty-eight working-class breastfeeding mothers across selected LGAs. A cross-sectional descriptive design was adopted for the study using an interviewer-based questionnaire. Data were analyzed using SPSS version 25.0 Descriptive analyses were done with frequencies and summary statistics. All analyses were done at a 95% confidence interval and the p-value was set at less than 0.05 significant level.The majority of the participants (54.1%) were between 20 and 29 years, 33% were government employees and 29.7% were employed in private sector. It was observed that 37% had good practice of exclusive breastfeeding while the majority (63%) had poor practice. Reported factors preventing the good practice of EBF by participants include insufficient breastmilk (64.1%), breast problems (58.9%), very tight work schedule (56.9%), maternal health issues (55%), end of maternity leave and inappropriate place for breastfeeding (53.1%). The job status of mothers was observed as one of the significant challenges faced by breastfeeding mothers, however not the prevailing problem as observed. The level of practice of exclusive breastfeeding among working-class mothers which was found to be poor is closely linked to their work schedule.